Effects of Oil Warm up Acceleration on the Fuel Consumption of Reciprocating Internal Combustion Engines - Cipollone, Roberto; Di Battista, Davide; Mauriello, Marco (Energy procedia, 2015)
The homologation cycle of vehicles for private passenger transportation or for light duty applications considers a cold start from ambient temperature. The most part of harmful substances (≈ 60-65%) are produced during the thermal engine stabilization which occurs in the very of the driving cycle. This strongly influences also engine efficiency, i.e. fuel consumption. The more recent commitments on CO2, therefore, reinforce the concept of reducing warm up time encountering it in the low carbon engine technologies. Due to this importance, engine thermal management has been the subject of a huge interest opening the way to new components, technologies and control strategies. This regards not only the coolant fluid, which undoubtedly influences engine warm up, but also the lubricant:an its heating acceleration produces much faster benefits.. The purpose of this paper is to assess the effect of a faster oil heating during the homologation cycle on the fuel consumption. An experimental campaign has been done on an 3L Iveco F1C engine mounted on a dynamometer test bench operated in order to reproduce the NEDC. The engine OEM has been characterized and the effect of the oil temperature has been studied according to: (a) an external heat source which brings the oil at its stabilized temperature value before engine start, (b) an internal heat source represented by the exhaust gases which almost immediately reach a temperature value able to heat-up the oil. The effects on CO2 emissions during the cycle have been evaluated. The benefits are noteworthy and justify some oil circuit modifications.